The Role Of The State In Conducting Civil Suits In The Results Of Corruption Controlled By The Heirs Of The Perpetrators Of Corruption - Sitompul, Ariman (Pena Justisia: Media Komunikasi dan Kajian Hukum, 2024)
Corruption is a very serious problem because it harms the country's finances. By therefore, several measures are needed to restore the financial losses of the state by make money payments in lieu of loss of state assets. This study aims to determine responsibility of heirs in the return of state assets from corruption committed by parents who have died and analyze the mechanism of payment of replacement money return of state assets resulting from corruption. This study uses normative research with a legal approach. The analysis showed that the responsibility of heirs in return of state assets, depending on the evidence of court decisions and mechanisms regarding replacement money in the return of state assets in accordance with the amount of property convicted of corruption. In other words, the mechanism substitute money for the return of state assets from the proceeds of corruption in Law Number 31 Year 1999 Jo Law No. 20 Of 2001 On The Eradication Of Corruption explain corruption convicts are obliged to pay the amount of replacement money according to the results of the corruption by convict. Conclusion that the state financial losses caused by corruption convicts who have the deceased is transferred to his heirs according to the evidence in the court decision.